Analysis on Double Quench and Instantaneous Power of SFCL Using Two Magnetically Coupled Windings According to Winding Direction - Seok-Cheol Ko; Tae-Hee Han; Sung-Hun Lim (Energies, 2020)
In this study, the characteristics of the double quench and instantaneous power of a superconducting fault current limiter (SFCL) using two magnetically coupled windings were analyzed. In the proposed model of SFCL, two magnetically coupled windings are wound on the iron core and each winding is connected to one superconducting element. When a fault occurs, the SFCL can limit the fault current by the double quench occurrence of two superconducting elements. In order to analyze the influence of the winding direction on the fault current limiting characteristics of the proposed SFCL, two magnetically coupled windings were designed to allow the same and the reverse directions. From the simulated short circuit experiment, the currents and the voltages of two coupled windings and two superconducting elements were measured and the instantaneous power and the double quench occurrence were analyzed. It was confirmed from the experimental results analysis that the fault current limiting characteristics of the SFCL were more favorable in the reverse winding direction than in the same winding direction.